Β-Cyclodextrin polymer as a linker to fabricate ternary nanocomposites AuNPs/pATP-β-CDP/rGO and their electrochemical application. (30th March 2015) - Chen, Ming; Shen, Xiao; Liu, Peipei; Wei, Ying; Meng, Yang; Zheng, Gang; Diao, Guowang
Highlights: β-Cyclodextrin polymer is used as a linker to prepare grapheme composites. Amount and dispersity of AuNPs on rGO can be adjusted by changing the concentration of pATP. Composites display high electrochemical response toward IDP and good catalytic property for ORR. The method describes an effective process for fabrication rGO composites. Abstract: Based on the self-assembly strategy, β-cyclodextrin polymer (β-CDP) was used as a linker to connect reduced graphene oxide (rGO) and p -aminothiophenol (pATP). Then, pre-prepared gold nanoparticles (AuNPs) can self-assemble onto the surface of pATP-β-CDP/rGO to obtain new ternary nanocomposites AuNPs/pATP-β-CDP/rGO. The amount or the density of AuNPs can be adjusted by changing the concentration of pATP. UV–vis and 1 H NMR spectra confirmed the formation of inclusion complex between pATP and β-CDP. β-CDP might improve the dispersity of rGO in aqueous and the surface property of rGO. AuNPs/pATP-β-CDP/rGO modified electrode displayed high electrochemical response toward a pesticide-imidacloprid (IDP). The enrichment capability and molecular recognition of β-CDP and the catalytic property of AuNPs for IDP molecules synergistically promoted the electrochemical response of rGO modified electrode. Additionally, ternary nanocomposites exhibited the good electrocatalytic performance for oxygen reduction in O2 -saturated 0.1 M H2 SO4 solution. The proposed synthesis strategy provided a facile, feasible and effective method for development of electrochemical sensors and Au-based catalysts for fuel cells.